# Expanding Algebraic Expressions: Multiplication

Contributed by:
This pdf includes the following topics:-
Expanding or removing brackets
Single brackets
Multiplying together two bracketed terms
Examples and many more.
1. Expanding or removing brackets
mc-expandbrack-2009-1
In this leaflet we see how to expand an expression containing brackets. By this we mean to rewrite
the expression in an equivalent form without any brackets in.
Single brackets
If we have a number, or a single algebraic term, multiplying bracketed terms, then all terms in the
brackets must be multiplied as shown in the following examples.
a(b + c) = ab + ac a(b − c) = ab − ac
Example Example
Expand 3(x + 2). Expand x(x − y).
The 3 outside must multiply both terms inside The x outside must multiply both terms inside
the brackets: the brackets:
3(x + 2) = 3x + 6 x(x − y) = x2 − xy
Example Example
Expand −3a2 (3 − b). Expand (x + 5)x.
Both terms inside the brackets must be multi- Here, the brackets appear first, but the prin-
plied by −3a2 : ciple is the same. Both terms inside must be
multiplied by the x outside:
−3a2 (3 − b) = −9a2 + 3a2 b (x + 5)x = x2 + 5x
1. Remove the brackets from the following expressions.
a) 5(x + 4) b) 2(y − 3) c) 4(3 − a) d) x(2 + x) e) p(q + 3)
f) −3(2 + a) g) s(t − s) h) −2(b − 3) i) 5a(2b + 3c) j) −y(2x − 5y)
www.mathcentre.ac.uk 1 c mathcentre 2009
2. Multiplying together two bracketed terms
Supppose we want to multiply out expressions where there are two brackets multiplying each other,
for example, (x + 5)(x + 10). We imagine that the term (x + 5) is a single quantity and use it to
multiply both the x and the 10 in the second pair of brackets:
(x + 5)(x + 10) = (x + 5)x + (x + 5)10
= x2 + 5x + 10x + 50
= x2 + 15x + 50
Having seen how to do this, we can shorten the process; to find (x + 5)(x + 10) we must ensure that
each term in the first bracket multiplies each term in the second. The arrows in the figure below
help us to see that all terms have been taken into account:
(x + 5)(x + 10) = x2 + 10x + 5x + 50 = x2 + 15x + 50
More generally
(x + a)(x + b) = x2 + xb + ax + ab = x2 + (a+b)x + ab
Example Example
Expand (x − 7)(x − 10). Expand (2x − 3)(x + 1).
(x − 7)(x − 10) = x2 − 10x − 7x + 70 (2x − 3)(x + 1) = 2x2 + 2x − 3x − 3
= x2 − 17x + 70 = 2x2 − x − 3
Example Example
Expand (x + 6)(x − 6). Expand (3x − 2)(3x + 2).
(x + 6)(x − 6) = x2 − 6x + 6x − 36 (3x − 2)(3x + 2) = 9x2 + 6x − 6x − 4
= x2 − 36 = 9x2 − 4
2. Expand each of the following.
a) (x + 2)(x + 3) b) (a + b)(c + 3) c) (y − 3)(y + 2)
d) (2x + 1)(3x − 2) e) (3x − 1)(3x + 1) f) (5x − 1)(x − 5)
2
g) (2p + 3q)(5p − 2q) h) (x + 2)(2x − x − 1)
a) 5x + 20 b) 2y − 6 c) 12 − 4a d) 2x + x2 e) pq + 3p
1.
f) −6 − 3a g) st − s2 h) −2b + 6 i) 10ab + 15ac j) −2xy + 5y 2
a) x2 + 5x + 6 b) ac + 3a + bc + 3b c) y2 − y − 6 d) 6x2 − x − 2
2.
e) 9x2 − 1 f) 5x2 − 26x + 5 g) 10p2 + 11pq − 6q 2 h) 2x3 + 3x2 − 3x − 2
www.mathcentre.ac.uk 2 c mathcentre 2009